2022
DOI: 10.1002/acn3.51498
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and abnormal cerebrospinal fluid associate with cognitive symptoms after mild COVID‐19

Abstract: Cognitive post‐acute sequelae of SARS‐CoV‐2 (PASC) can occur after mild COVID‐19. Detailed clinical characterizations may inform pathogenesis. We evaluated 22 adults reporting cognitive PASC and 10 not reporting cognitive symptoms after mild SARS‐CoV‐2 infection through structured interviews, neuropsychological testing, and optional cerebrospinal fluid (CSF) evaluations (53%). Delayed onset of cognitive PASC occurred in 43% and associated with younger age. Cognitive PASC participants had a higher number of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 21 publications
2
57
0
1
Order By: Relevance
“…These include innate and adaptive immune dysregulation [17][18][19][20], autoimmunity [21][22][23], human herpes virus reactivation [24], and microvascular dysfunction [25,26], among others [24]. Certain sociodemographic factors (e.g., income status, access to care) [27,28] and a greater number and/or certain types of medical comorbidities (e.g., obesity, diabetes mellitus, pre-existing cardiovascular or neurologic disease) [27,29,30] may also increase the likelihood of an individual developing PASC. Higher prevalence of such factors among PWH [31,32], along with differences in immune responses to SARS-CoV-2 [14,15] and chronic inflammation and immune dysregulation even in the presence of antiretroviral therapy [33][34][35][36][37][38][39], may make PWH selectively vulnerable to developing persistent COVID-19-attributed symptoms following SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…These include innate and adaptive immune dysregulation [17][18][19][20], autoimmunity [21][22][23], human herpes virus reactivation [24], and microvascular dysfunction [25,26], among others [24]. Certain sociodemographic factors (e.g., income status, access to care) [27,28] and a greater number and/or certain types of medical comorbidities (e.g., obesity, diabetes mellitus, pre-existing cardiovascular or neurologic disease) [27,29,30] may also increase the likelihood of an individual developing PASC. Higher prevalence of such factors among PWH [31,32], along with differences in immune responses to SARS-CoV-2 [14,15] and chronic inflammation and immune dysregulation even in the presence of antiretroviral therapy [33][34][35][36][37][38][39], may make PWH selectively vulnerable to developing persistent COVID-19-attributed symptoms following SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Over 75% of 18 patients in a study with mild to moderate disease were found to have the cognitive deficits listed above, indicating that cognitive impairment can even effect those with mild disease [ 26 ]. Cognitive impairments in areas of working memory, executive functioning, memory, visuospatial ability, abstraction, and orientation have also been found [ 17 , 27 ]. Recovery in some or most of these areas in the post-acute phase of the illness has been demonstrated [ 28 ]; however, there are persisting deficits seen in this phase, including patients who were not hospitalized [ 29 ].…”
Section: Neurocognitive and Functional Outcomementioning
confidence: 99%
“…A neuropsychological evaluation can be useful in determining areas of decrement in order to direct treatments, including recommendations for psychotherapy, medication management, and physical, speech, and occupational therapies [ 33 ]. Objective cognitive assessments have been found as a more reliable means to detect the presence of cognitive PASC versus subjective assessment or self-report [ 27 ].…”
Section: Neurocognitive and Functional Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of post-COVID syndrome remains unknown. Several mechanisms have been suggested, including prolonged inflammation, vascular injury and endothelial dysfunction, sequelae of organ damage, and the effects of hospitalisation [ 4 , 5 , 6 ]. Due to the heterogeneity of clinical symptoms, multiple mechanisms may be involved.…”
Section: Introductionmentioning
confidence: 99%